EXPLORING TEACHER’S AND STUDENTS’ BELIEFS CONCERNING HIGHER ORDER THINKING IN MATHEMATICS - Elizar Elizar; Cut Khairunnisak (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2022)
Teacher beliefs play a fundamental role in mathematics teaching and learning, as they will ultimately influence the teacher's classroom practices. Student beliefs on a subject matter also hold equal importance as they will be reflected in how the students approach the learning and related issues to the subject. The importance of research on teachers' beliefs stems from the possible relationship between teacher beliefs and student beliefs. This descriptive quantitative study aimed to measure the degree of conformity between teacher and student beliefs concerning mathematics related to Higher Order Thinking (HOT) and Lower Order Thinking (LOT). The population was all Year 9 students in Aceh, Indonesia, and the samples were 1135 Year 9 students and 46 Year 9 mathematics teachers from 25 schools selected through stratified random sampling. Data collection was obtained through teacher and student questionnaires, and data were analyzed descriptively by SPSS 20. The finding of this study revealed that teacher beliefs concerning mathematics related to HOT were highly positive (83%). While the percentage of students who hold highly positive beliefs concerning mathematics related to HOT was just over 50%, indicating the discrepancy between teacher and student beliefs. However, regarding the beliefs concerning mathematics related to LOT, teacher and student beliefs conformed; they had somewhat positive beliefs (68% and 71.30%, respectively). This study implies that teachers need to promote HOTS in mathematics teaching at schools to foster students’ positive beliefs toward HOT.